DEVELOPING INTERACTIVE CANVA MEDIA: ANIMAL LIFE CYCLES FOR 3RD GRADE IN SCIENCE AND SOCIAL SUBJECTS - Afifa, Afifa; Sriwijayanti, Ribut Prastiwi; Jannah, Faridahtul (JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
This research aims to develop an interactive learning media based on Canva for teaching the life cycle of animals to third-grade students at SDN Kebonsari Kulon 1 Probolinggo. The feasibility and practicality of the media were evaluated based on assessments from media experts, materials experts, learning practitioners, and student response questionnaires. This research utilized the Research and Development (R&D) method proposed by William Lee. Researchers chose this method because the existing media lacked variety, relying just on textbooks and PowerPoint (PPT). The researcher selected the ADDIE model, which includes five stages: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. Researchers conducted the research in the 3rd grade of SDN Kebonsari Kulon 1 Probolinggo. This research conducted Interviews and observations as the initial needs analysis and employed validation and student response questionnaires for data collection. The results of the product trial research indicated a high level of feasibility and practicality, with scores of 96% from media validators, 89.09% from material experts, and 98.46% from learning practitioners. Additionally, the results of student responses showed a high level of media feasibility, with 96.3% in small groups and 94.1% in large groups, categorized as very feasible